Osteoporosis: Etiologi hingga Tatalaksana - Ilma Puteri Hutami; Anisa Nuraisa Djausal (CV. Jasa Sukses Abadi, 2023)
One of the main public health problems for the elderly, both men and women, is osteoporosis. Many factors accompany problems in the elderly such as aging, menopause, endocrine disorders, weakening of physical activity, as well as side effects of certain drugs, which contribute to complaints of osteoporosis. The presence of osteoporosis results in increased bone fragility while almost all bones are susceptible to fracture. The incidence of fracture events is closely related to the increase in osteoporosis which is indicated by increasing age. Measures to diagnose and prevent osteoporosis and its complications are a major issue and concern at this time as an effort in public health because the increased incidence of fractures is also associated with increasing health care costs and accompanied by physical disability and impaired quality of life, even the effect has an impact on increasing mortality rate. Currently, BMD (bone mass density) measurement is a key factor in identifying patients at risk of fracture. The measurement results of BMD are used as a reference for making treatment therapy decisions, as well as for monitoring the progress of the therapy being undertaken. Several risk factors for osteoporosis have also been identified for their treatment potential, which can be modified and cannot be modified. Treatment of potentially modifiable risk factors along with sports activities accompanied by calcium (Ca) and vitamin D supplements is important information for the management or pharmacological management of osteoporosis.